The city school urdu ki amli kitab kg miyad awal (Albakio International,The City school Lahore, 2015)
"Urdu Ki Amli" is a comprehensive book that teaches the fundamental rules and writing skills of the Urdu language. It emphasizes vocabulary, sentence structure, and literary principles. This book serves as a valuable resource for students, particularly in enhancing their writing and speaking abilities in Urdu.